Cooperation and Empire Local Realities of Global Processes - Bührer, Tanja 1974- (Berghahn Books, Incorporated, 2017)
Cooperation and Empire -- Contents -- Figures and Tables -- Introduction. Cooperation and Empire -- Chapter 1. Caciques - Indigenous Rulers and the Colonial Regime in Yucatán in the Sixteenth Century -- Chapter 2. Connecting Worlds -- Chapter 3. Cooperation and Cultural Adaption -- Chapter 4. Local Cooperation in a Subversive Colony -- Chapter 5. Uncle Toms and Kupapas -- Chapter 6. 'Collaboration' or Sabotage? -- Chapter 7. Chieftaincy as a Political Resource in the German Colony of Cameroon, 1884-1916 -- Chapter 8. Cooperation at its Limits -- Chapter 9. Key Alliance? -- Chapter 10. The Cooperation between the British and Faisal I of Iraq (1921-1932) -- Chapter 11. Collaborating on Unequal Terms -- Chapter 12. Indigenous Agents of Colonial Rule in Africa and India -- Chapter 13. Indigenous Cooperation -- Index